Bringing PROMIS to Early Childhood: Introduction and Qualitative Methods for the Development of Early Childhood Parent Report Instruments. (4th April 2022) - Cella, David; Blackwell, Courtney K; Wakschlag, Lauren S
Abstract: Objective: Provide an overview of the Patient-Reported Outcomes Measurement Information System (PROMIS ® ) Early Childhood Parent Report measurement development project and describe its qualitative methods. Methods: The PROMIS Early Childhood (PROMIS EC) initiative used the PROMIS mixed-methods approach to patient-reported outcome development, with insight from the developmental specification framework to create parent report measures appropriate for assessing young children's health-related quality of life. Qualitative methods to develop these instruments included expert input, literature and measure review, and parent concept elicitation and cognitive interviews to confirm the measure frameworks, item understandability, and developmental appropriateness. Results: Twelve measures resulted from the PROMIS EC initiative. These parent report instruments cover young children's physical, mental, and social health. Conclusions: The new PROMIS EC Parent Report instruments offer clinicians and researchers brief and psychometrically robust tools to evaluate young children's physical, mental, and social health outcomes. Aligned with the PROMIS Pediatric instruments, the early childhood versions enable coherent lifespan measurement starting at age 1 while maintaining developmental sensitivity.